2022
DOI: 10.3390/vaccines10091448
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Glioma Cancer Treatment: Conventional and Epigenetic Realms

Abstract: Glioblastoma (GBM) is the most typical and aggressive form of primary brain tumor in adults, with a poor prognosis. Successful glioma treatment is hampered by ineffective medication distribution across the blood-brain barrier (BBB) and the emergence of drug resistance. Although a few FDA-approved multimodal treatments are available for glioblastoma, most patients still have poor prognoses. Targeting epigenetic variables, immunotherapy, gene therapy, and different vaccine- and peptide-based treatments are some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 364 publications
1
3
0
Order By: Relevance
“…In our study, the reduction of H3K27me3 levels in OPCs with p53 deletion and PDGF-BB overexpression, by treatment with a well-recognized EZH2 inhibitor (Tazemetostat), significantly reduced the expression of genes regulating cell division, while increasing the expression of genes related to differentiation, thereby providing a molecular rationale to previous studies on the prognostic value of H3K27me3 56,57 . Our data are also consistent with the beneficial effect of reduced EZH2 activity on decreasing proliferation and reducing tumor growth in animal models 58,59,60 and decreasing proliferation and migration in adult human glioma cells 61 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the reduction of H3K27me3 levels in OPCs with p53 deletion and PDGF-BB overexpression, by treatment with a well-recognized EZH2 inhibitor (Tazemetostat), significantly reduced the expression of genes regulating cell division, while increasing the expression of genes related to differentiation, thereby providing a molecular rationale to previous studies on the prognostic value of H3K27me3 56,57 . Our data are also consistent with the beneficial effect of reduced EZH2 activity on decreasing proliferation and reducing tumor growth in animal models 58,59,60 and decreasing proliferation and migration in adult human glioma cells 61 .…”
Section: Discussionsupporting
confidence: 89%
“…The p14 ARF gene is a tumor-suppressor gene involved in regulating cell proliferation and division [290,291], as well as tumor-induced angiogenesis [292,293]. When hypermethylation occurs in the p14 ARF gene, it leads to the inactivation of its tumor-suppressor functions, including the loss of p53 function and the deactivation of p21-mediated cell proliferation control [294].…”
Section: Cdkn2amentioning
confidence: 99%
“…This reduction in p16 INK4a levels can disrupt the normal regulation of the cell cycle, potentially leading to uncontrolled cell growth and an increased risk of developing cancer. The methylation rate of CDKN2A has been extensively studied in various types of cancer [291,301,302]. The reported incidence of p16 INK4a hypermethylation in OSCC can range from 23% to 76%.…”
Section: Cdkn2amentioning
confidence: 99%
“…Further, in preclinical studies, IFN-β has been reported to enhance the chemosensitivity towards TMZ by reducing transcription of MGMT [159]. It was also reported that the addition of IFN-β to standard chemoradiotherapy with TMZ (phase I clinical trial) was well tolerated and enhanced the survival of GBM patients [160], but no meaningful efficacy in cases of GBM or pediatric HGG, was noted after combined therapy with IFN-γ and radiotherapy or chemoradiotherapy [161].…”
Section: Immunotherapy and Clinical Trials In Gbm Malignancymentioning
confidence: 99%